Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Badan Usaha Milik Negara (BUMN) Yang Terdaftar Pada Bursa Efek Indonesia (BEI) Tahun 2017 - 2019 - Pandu Wiratama; Gideon Setyo Budiwitjaksono (STIE Mandala Jember, 2021)
The aim of this research is to provide empirical evidence the effect of firm size, leverage, profitability, Chief Executive Officer (CEO) educational background, and Chief Executive Officer (CEO) in the final year of his services on earnings management. The population in this study are State-Owned Enterprises (SOE) listed on the Indonesia Stock Exchange (IDX) 2017 - 2019. This research used 16 State-Owned Enterprises (SOE), selected using purposive sampling method. Data were analyzed using multiple regression. Based on the result of analysis concluded that all the independent variables, firm size, size, leverage, profitability, Chief Executive Officer (CEO) educational background, and Chief Executive Officer (CEO) in the final year of his services had no significant effect on earnings management. Keywords: Earnings management, Firm size, Leverage, Profitability, CEO educational background, and CEO in the final year of his services